PENGARUH KEPUASAN KERJA, STRES KERJA, DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA HEAD OFFICE PT. THAMRIN BROTHERS PALEMBANG - Ulil Amri; Agustina Marzuki; Steven Riyanto (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study aims to determine the effect of Job Satisfaction, Job Stress and Organizational Commitment on Turnover Intention at Head Office PT. Thamrin Brothers Palembang. In this study a total population of 145 people. Based on the calculation formula Slovin, the number of samples obtained in this study as many as 60 people. The samples in this study using Accidental Sampling.From these results simultaneously variable Job Satisfaction, Job Stress and Organizational Commitment jointly affect the Turnover Intention, it can be seen from the Test sig F F where the value of 0.000 <α (0.05). Working in partial satisfaction has a negative and significant effect on Turnover Intention indicated by coefficient - 0,156 and sig t of 0.002 <α (0.05). Variables Job Stress has positive and significant influence on Turnover Intention indicated by the coefficient of 0.161 and sig t of 0.000 <α (0.05) and Organizational Commitment variable has a significant negative influence and partially on Turnover Intention indicated by value coefficient - 0.143 and sig t 0,001 <α (0.05). The correlation coefficient of 0.748 means indicates a very strong relationship and significant. To find out how much influence can be seen from the value of determination R Square of 0, 559. Turnover Intention Variables can be explained or there are significant variables Job Satisfaction, Job Stress and Organizational Commitment, while the rest influenced by other factors not examined. Implementation is an effort to increase job satisfaction, such as giving the opportunity of employees to use their skills and abilities, providing appropriate salary, increase incentives, leaders apply the appropriate style of leadership, maintaining a good relationship between co-workers, and provide promotion policy against employees who achievement. Attempts to lower the Job Stress, such as reducing the workload, providing a longer working time according their work, improve feedback and give authority over the responsibilities of the job. Efforts to improve the Organization's commitment, as is involving employees in the organization, to convince employees to survive, fulfill obligations to the organization's employees. Keywords : Job Satisfaction, Stress Work, Organizational Commitment, Turnover Intention